Recurrent flaccid paralysis due to hypokalemia as an unusual presentation of hypothyroidism - Nainggolan, Prima Heptayana; Meliala, Terang (Program Studi Magister Kesehatan Masyarakat Universitas Prima Indonesia, 2025)
Background: Recurrent flaccid paralysis with low level of potassium can be found in hypokalemic periodic paralysis or thyrotoxic periodic paralysis. Hypokalemic Periodic paralysis associated with hypothyroidism is rare in the existing literature. Case illustration: A 41-year-old man had been admitted to the emergency ward due to weakness of his lower extremities for 3 days before the admission. He had the same symptoms one year ago. Based on the physical examination, decreases in both muscle strength and physiological reflexes in lower extremities had been found. From laboratory examination, the serum potassium level had reduced up to 1,7 mmol/l, with high TSHs and normal T3 and T4 level. The nerve conduction studies had revealed normal limits. Following a potassium correction, the patient had shown improvement. Discussion: In most cases, hypokalemic periodic paralysis is caused by pure hypokalemia or high thyroid hormone level in serum (as in thyrotoxic periodic paralysis). However, this patient was diagnosed as hypokalemic periodic paralysis with subclinical hypothyroidism. This case is therefore a very rare and unusual presentation of hypothyroidism. The relation between hypokalemic periodic paralysis and hypothyroidism remains unclear. Conclusion: Hypokalemic periodic paralysis associated with hypothyroidism is rare and understanding about this condition has not been established thus far in the literature. Thyroid examination is needed for patients with hypokalemic periodic paralysis.